UPAYA HUKUM DAN PEMULIHAN HAK SAHAM MINORITAS PASCA PUTUSAN PENGADILAN: STUDI ATAS PERLINDUNGAN INVESTOR DI INDONESIA - Ali Abdullah; Liesmawati Liesmawati (Universitas Labuhanbatu, 2025)
Restoration of minority shareholder rights in private limited companies is often ineffective, despite court decisions confirming a breach of fiduciary duty. This situation indicates a gap between the legal protection norms in Law Number 40 of 2007 concerning Limited Liability Companies and their implementation in practice. This study analyzes the effectiveness of the mechanism for restoring minority shareholder rights following a court decision. The results show that court decisions are generally declarative and poorly enforced, making them difficult to implement. Key obstacles include resistance from majority shareholders, weak institutional coordination, and low transparency in private companies. This study recommends the formulation of more operational rulings, strengthening implementation oversight, and integrating legal technology with a restorative justice approach. Using a juridical-empirical approach, this study contributes to strengthening legal protection for minority shareholders and increasing legal certainty in corporate practice.Keywords: Minority Shareholders, Fiduciary Duty, Legal Remedies